Activation of endothelial cells by extracellular vesicles derived from Mycobacterium tuberculosis infected macrophages or mice. - Li Li (PLoS ONE, 2018)
Endothelial cells play an essential role in regulating an immune response through promoting leukocyte adhesion and cell migration and production of cytokines such as TNFα. Regulation of endothelial cell immune function is tightly regulated and recent studies suggest that extracellular vesicles (EVs) are prominently involved in this process. However, the importance of EVs in regulating endothelial activation in the context of a bacterial infection is poorly understood. To begin addressing this knowledge gap we characterized the endothelial cell response to EVs released from Mycobacterium tuberculosis (Mtb) infected macrophages. Our result showed increased macrophage migration through the monolayer when endothelial cells were pretreated with EVs isolated from Mtb-infected macrophages. Transcriptome analysis showed a significant upregulation of genes involved in cell adhesion and the inflammatory process in endothelial cells treated with EVs. These results were validated by quantitative PCR and flow cytometry. Pathway analysis of these differentially expressed genes indicated that several immune response-related pathways were up-regulated. Endothelial cells were also treated with EVs isolated from the serum of Mtb-infected mice. Interestingly, EVs isolated 14 days but not 7 or 21 days post-infection showed a similar ability to induce endothelial cell activation suggesting a change in EV function during the course of an Mtb infection. Immunofluorescence microscopy result indicated that NF-κB and the Type 1 interferon pathways were involved in endothelial activation by EVs. In summary, our data suggest that EVs can activate endothelial cells and thus may play an important role in modulating host immune responses during an Mtb infection.